2016
DOI: 10.1186/s12967-016-0976-8
|View full text |Cite
|
Sign up to set email alerts
|

In vivo monitoring of lung inflammation in CFTR-deficient mice

Abstract: BackgroundExperimentally, lung inflammation in laboratory animals is usually detected by the presence of inflammatory markers, such as immune cells and cytokines, in the bronchoalveolar lavage fluid (BALF) of sacrificed animals. This method, although extensively used, is time, money and animal life consuming, especially when applied to genetically modified animals. Thus a new and more convenient approach, based on in vivo imaging analysis, has been set up to evaluate the inflammatory response in the lung of CF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…To evaluate in vivo the possible reduction of inflammation associated with inhibition of P. aeruginosa virulence exoproducts, we used a transgenic mouse model that was previously validated [15,37,38]. In presence of lung inflammatory response induced by non-invasive intratracheal challenge with culture supernatant, the exogenous IL-8 promoter is recognized by the mouse transcriptional apparatus and luciferase enzyme is produced.…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate in vivo the possible reduction of inflammation associated with inhibition of P. aeruginosa virulence exoproducts, we used a transgenic mouse model that was previously validated [15,37,38]. In presence of lung inflammatory response induced by non-invasive intratracheal challenge with culture supernatant, the exogenous IL-8 promoter is recognized by the mouse transcriptional apparatus and luciferase enzyme is produced.…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that CFTR has been widely studied in cystic brosis (CF) and recently, it has grown interest in to study its role in other diseases or in ammatory conditions such as in the biliary epithelium and intestine 12,22−24 . In animal models and in vitro studies have demonstrated the role of CFTR in the intestinal in ammatory process characterized by histological in ltration of immune cells and increased of in ammatory fecal biomarkers [13][14][15][16] .…”
Section: Discussionmentioning
confidence: 99%
“…In patients with CF has been observed an increase of fecal calprotectin as same as happens in the in ammatory bowel disease (IBD) [13][14][15] . The ABCC7/CFTR knock-out mice model developed intestinal in ammation suggesting a role of this gene in the gut in ammation 12,16 . The levels of ABCC7/CFTR expression have been involved in modulating the NF-ĸB activity and the production of IL8 and IL6 production in lung cell lines [17][18][19] .…”
Section: Introductionmentioning
confidence: 99%
“…In the past project we shown that the antibiotic azithromycin causes a significant decrease of the lung inflammation in that is capable of inhibiting the synthesis of bacterial virulence factors. Azithromycin is extensively used in cystic fibrosis as an anti-inflammatory molecule but several cases of azithromycin resistance have been reported [1][2], especially in patients using the drug for long times. It seems then important to identify other therapeutic agents to be used in nonresponding patients.…”
Section: Hypothesis and Objectivesmentioning
confidence: 99%
“…Background.The possibility of monitoring the inflammatory response in a IL-8 transgenic WT and CFTRknockout (CF), non invasive, animal model has been demonstrated in a previous project conducted by us [1,2].…”
mentioning
confidence: 99%